USING WHATSAPP APPLICATION IN TEACHING READING SKILL AT THE SEVENTH GRADE OF SMP N 18 SURAKARTA - Ageftia Nawang Suhita; Sri Handayani (English Education Department Slamet Riyadi University Surakarta, 2021)
This research was aimed at :(1) the application of using WhatsApp in teaching reading skill at the Seventh Grade students SMP N 18 Surakarta in the academic year 2019/2020 (2) the students problems faced by the student in teaching reading skill at the seventh grade students of SMP N 18 Surakarta in the Academic year 2019/2020. This research was conducted fromJuly to August2020. The researcher took 29 students of SMP N 18 Surakarta as the sample.A descriptive qualitative research was used in this study. The subject of thisresearch was the seventh grade students’of SMP N 18 Surakarta the 2019/2020 academic year. To collect the data, the researcher used questionnaire, link sent by WhatsApp Group. Interview with the teacher face-to-face, interview with the teacher by using WhatsApp Video Call .To validity data, the researcher used data triangulation. The result of the research show that: 1)The main problems of learning English was lack of student motivations. Insufficient time also was the problems in learning English. 2) The internet connection can influenced online learning process. 3) Students and teacher discussion usedWhatsApp, work in pairs in online learning. 4) Students submitted the assignment by sent files through WhatsApp. 4) There were problems in online learning such as internet connection, internet quota, student’s slow in response and parents guidance. 5) The teacher used features picture, video, document to clarify the material. Keywords :WhatsApp, Online Learning, Descriptive Qualitative Research